2017
DOI: 10.1371/journal.pone.0188045
|View full text |Cite
|
Sign up to set email alerts
|

Soluble CD40 ligand directly alters glomerular permeability and may act as a circulating permeability factor in FSGS

Abstract: CD40/CD40 ligand (CD40L) dyad, a co-stimulatory bi-molecular complex involved in the adaptive immune response, has also potent pro-inflammatory actions in haematopoietic and non-haematopoietic cells. We describe here a novel role for soluble CD40L (sCD40L) as modifier of glomerular permselectivity directly acting on glomerular epithelial cells (GECs). We found that stimulation of CD40, constitutively expressed on GEC cell membrane, by the sCD40L rapidly induced redistribution and loss of nephrin in GECs, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 64 publications
(77 reference statements)
0
32
0
Order By: Relevance
“…In another study (published in 2017), Doublier et al [43] found that sCD40L, a protein within the tumor-necrosis factor family, was significantly increased in the sera of children with steroid-sensitive and steroid-resistant nephrotic syndrome, and in adults with biopsy-proven FSGS compared to healthy subjects, but not in children with congenital nephrotic syndrome or patients with membranous nephropathy [43]. Interactions between sCD40L and CD40 (present on podocytes) are responsible for the reduced expression of nephrin on podocytes and induce albumin leakage in the urine.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In another study (published in 2017), Doublier et al [43] found that sCD40L, a protein within the tumor-necrosis factor family, was significantly increased in the sera of children with steroid-sensitive and steroid-resistant nephrotic syndrome, and in adults with biopsy-proven FSGS compared to healthy subjects, but not in children with congenital nephrotic syndrome or patients with membranous nephropathy [43]. Interactions between sCD40L and CD40 (present on podocytes) are responsible for the reduced expression of nephrin on podocytes and induce albumin leakage in the urine.…”
Section: Discussionmentioning
confidence: 93%
“…Interactions between sCD40L and CD40 (present on podocytes) are responsible for the reduced expression of nephrin on podocytes and induce albumin leakage in the urine. Doublier et al [43] also reported inhibition of this interaction by pretreatment with the inhibiting fusion protein CD40-mulg, the use of the neutralizing anti-CD40L antibody, or the fusion protein CD40-muCD8, which could block the disappearance of nephrin from the podocyte membrane and thereby prevent albuminuria.…”
Section: Discussionmentioning
confidence: 99%
“…The CD40/CD40L complex mediates, at several sites, pro-inflammatory events ( 91 ), including production of cytokines, chemoattractants, oxygen radicals, etc. CD40 is also constitutively expressed in podocytes, where activation by CD40L promotes redistribution of nephrin and increases permeability to albumin in isolated glomeruli ( 92 , 93 ). Previous studies showed that, in murine models of membranous nephropathy and lupus nephritis, CD40L blockade by anti-CD40L antibodies protects from autoimmune glomerulonephritis ( 94 , 95 ).…”
Section: Mechanisms 5 Specific Moleculesmentioning
confidence: 99%
“…“Phage opsonization” of T cells may interfere with their activation and eventually lead to their clearance from the circulation – a phenomenon similar to that occurring using anti-CD3 monoclonal antibody and anti-lymphocyte globulin treatment. KGD is also known to be present within the CD40 ligand (CD40L) which together with CD40 forms an important dyad relevant for mounting an immune response, autoimmunity, and inflammation; for example, its role has recently been suggested in immunopathology of certain forms of glomerulonephritis ( Doublier et al, 2017 ). All those data suggest that the KGD motif present in phages is functional and may mediate interactions of phages with cells of immune system relevant for the development of immune-mediated diseases.…”
Section: Potential Molecular Basis For Phage–integrin Interactionsmentioning
confidence: 99%